A Method of Collecting Eggs of Micromus tas'l1Wniae Walker (Neuroptera: Hemerobiidae) - Hussein, Mohd Yusof (1986)
A method of collecting the eggs of Micromus tasmaniae, an insect predator of the potato aphid attacking the potato plant is described. The method was adopted for use in the mass production of the eggs needed for field release trials. Prior tests conducted in the laboratory showed that a solution of sodium hypochlorite (NaC10) at either 0.75% or 1.00% concentration did not have detrimental effects on egg hatch after immersing th.em jor 6 or 10 minutes, respect~·vely. Seventy five percent (75%) of the eggs were removed from the cloth substrate and 95% of them hatched, Sodium hypochloride at 5% concentration caused the failure of all the eggs to hatch but all of the eggs were easily removed from the substrate. This method has reduced egg damage and collection time as compared to the conventional method whereby each egg is collected one by one.